1982
DOI: 10.1258/002367782781110232
|View full text |Cite
|
Sign up to set email alerts
|

Control of nephrocalcinosis by manipulating the calcium: phosphorus ratio in commercial rodent diets

Abstract: Changing the calcium: phosphorus ratio in 2 commercial diets from 0·73 and 0·84 to 1·25 and 1·20 reduced the incidence of nephrocalcinosis (which occurred almost entirely in female rats) virtually to nil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…Various synonyms for nephrocalcinosis include renal mineralization, mineralization of the kidney, calci cationkidney, phosphorus-induce d nephrocalcinosis, and phosphate crystals in tubules (15,16). These terms indicate that there is mineral deposition in the kidney and it appears to be associated with phosphorus and calcium.…”
Section: Nephrocalcinosismentioning
confidence: 99%
See 1 more Smart Citation
“…Various synonyms for nephrocalcinosis include renal mineralization, mineralization of the kidney, calci cationkidney, phosphorus-induce d nephrocalcinosis, and phosphate crystals in tubules (15,16). These terms indicate that there is mineral deposition in the kidney and it appears to be associated with phosphorus and calcium.…”
Section: Nephrocalcinosismentioning
confidence: 99%
“…These terms indicate that there is mineral deposition in the kidney and it appears to be associated with phosphorus and calcium. Nephrocalcinosis is mineralization of renal tubules at the corticomedullary junction (15,16). The histological appearance of a kidney with moderate nephrocalcinosis is shown in Figure 6.…”
Section: Nephrocalcinosismentioning
confidence: 99%
“…The incorporation of high amounts of fluoride into a high phosphorus or low magnesium diet protects against nephrocalcinosis (Luoma et al, 1976;Forbes, 1971). The incidence of kidney calcification in rats fed commercial diets can vary considerably (Cousins & Geary, 1966;Clapp, 1980;Clapp et al, 1982). A study showed that in rats fed 3 out of 6 commercial rat diets there was a high incidence of nephrocalcinosis (Clapp, 1980).…”
Section: Diet and Nephrocalcinosismentioning
confidence: 99%
“…Concerning the latter, of prime importance is the balance between the calcium, phosphorus and magnesium content of the diet. A common feature of all diets which induce nephrocalcinosis is a calcium: phosphorus ratio of 1 or less (Du Bruyn, 1970, 1972Hitchman, Hasany, Hitchman, Harrison & Tam, 1979;Clapp, 1980;Clapp et at. 1982;Harwood, 1982).…”
Section: A K J Al-modhefer and Othersmentioning
confidence: 99%
“…Most of the commonly used rat strains are affected by the condition, and the incidence of the lesion is consistently greater in females than males (see, for example, Forbes, 1963;Geary & Cousins, 1969;Goulding & Malthus, 1969;Woodard, 1971 a, b;Du Bruyn, 1972;Kaunitz & Johnson, 1976; Clapp, 1980;Clapp, Wade & Samuels, 1982;Harwood, 1982). In nephrocalcinosis, a precipitation of calcium phosphate occurs initially in proximal tubule brush borders.…”
Section: Introductionmentioning
confidence: 99%